Photo-spintronics of spin-orbit active electric weak links - Shekhter, R.I.; Entin-Wohlman, O.; Jonson, M.; Aharony, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We show that a carbon nanotube can serve as a functional electric weak link performing photo-spintronic transduction. A spin current, facilitated by strong spin-orbit interactions in the nanotube and not accompanied by a charge current, is induced in a device containing the nanotube weak link by circularly polarized microwaves. Nanomechanical tuning of the photo-spintronic transduction can be achieved due to the sensitivity of the spin-orbit interaction to geometrical deformations of the weak link.